2020
DOI: 10.1007/s00376-020-0088-5
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Global Warming and Atmospheric Circulation to the Hottest Spring in Eastern China in 2018

Abstract: The spring of 2018 was the hottest on record since 1951 over eastern China based on station observations, being 2.5°C higher than the 1961−90 mean and with more than 900 stations reaching the record spring mean temperature. This event exerted serious impacts in the region on agriculture, plant phenology, electricity transmission systems, and human health. In this paper, the contributions of human-induced climate change and anomalous anticyclonic circulation to this event are investigated using the newly homoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…These studies consistently show that anthropogenic forcings have substantially increased the probability of high-temperature events in China. While different factors including atmospheric circulation [ 88 ], sea surface temperature [ 89 ] and the effect of urbanization [ 90 ] have been considered, anthropogenic forcings appear to have played the dominant role in the increase in the magnitude and frequency of high-temperature events.…”
Section: Attribution Of Extreme Eventsmentioning
confidence: 99%
“…These studies consistently show that anthropogenic forcings have substantially increased the probability of high-temperature events in China. While different factors including atmospheric circulation [ 88 ], sea surface temperature [ 89 ] and the effect of urbanization [ 90 ] have been considered, anthropogenic forcings appear to have played the dominant role in the increase in the magnitude and frequency of high-temperature events.…”
Section: Attribution Of Extreme Eventsmentioning
confidence: 99%
“…Previous studies have shown that there are apparent early onset phenomena of EHEs in eastern China, especially in the past 10 years, and the range and intensity of EH days in May have increased signi cantly (Zang et al 2019;LU et al 2020, Wang et al 2021). Therefore, this paper analyses the average frequency of EHEs per station in four subregions from May to September since 1961 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The damage caused by large-scale and long-lasting PEHEs is higher than that of small-scale and short-duration PEHEs. Most studies on the duration of extreme events have de ned a threshold (LU et al 2020;Zhou et al 2020). For example, Wang et al (2013) and Wang et al (2018) de ned EHEs lasting more than 5 days as PEHEs.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, this paper only discussed the changing trend of meteorological drought in Northwest China and did not explore the main factors that led to the evolution of meteorological drought. In fact, the atmospheric circulation and the influence of human activities may cause climate change [40,41], thus leading to a spatiotemporal difference in drought. The next research should focus on the factors affecting the meteorological drought in Northwest China and pay attention to the correlation between the influencing factors and climate change.…”
Section: Shortage and Prospect Of The Present Studymentioning
confidence: 99%